Decoding the Brain: Neural Representation and the Limits of Multivariate Pattern Analysis in Cognitive Neuroscience. (6th September 2017) - Ritchie, J Brendan; Kaplan, David Michael; Klein, Colin
Abstract: Since its introduction, multivariate pattern analysis (MVPA), or 'neural decoding', has transformed the field of cognitive neuroscience. Underlying its influence is a crucial inference, which we call the decoder's dictum: if information can be decoded from patterns of neural activity, then this provides strong evidence about what information those patterns represent. Although the dictum is a widely held and well-motivated principle in decoding research, it has received scant philosophical attention. We critically evaluate the dictum, arguing that it is false: decodability is a poor guide for revealing the content of neural representations. However, we also suggest how the dictum can be improved on, in order to better justify inferences about neural representation using MVPA. 1 Introduction 2 A Brief Primer on Neural Decoding: Methods, Application, and Interpretation 2.1 What is multivariate pattern analysis? 2.2 The informational benefits of multivariate pattern analysis 3 Why the Decoder's Dictum Is False 3.1 We don't know what information is decoded 3.2 The theoretical basis for the dictum 3.3 Undermining the theoretical basis 4 Objections and Replies 4.1 Does anyone really believe the dictum? 4.2 Good decoding is not enough 4.3 Predicting behaviour is not enough 5 Moving beyond the Dictum 6 Conclusion